A lightweight, ceramicizable phthalonitrile aerogel and composites thereof and methods of making
Patent Information
- Application Number
- CN202610176937.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-06
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-02-06
AI Technical Summary
[0004]然而,邻苯二甲腈树脂的固化温度高、固化周期长,其溶胶-凝胶过程难以精确控制,导致直接制备结构均匀、密度可调且具有完整纳米网络的高性能气凝胶面临巨大挑战,现有技术难以采用邻苯二甲腈树脂直接制备具有完整纳米网络结构的邻苯二甲腈气凝胶
(1)本发明通过将邻苯二甲腈树脂与凝胶剂共同分散于极性非质子溶剂中,并加入固化剂混合形成溶胶,克服了单纯分散邻苯二甲腈树脂并添加固化剂无法形成稳定凝胶体系的技术障碍,这是因为邻苯二甲腈树脂不同于邻苯二甲腈单体,邻苯二甲腈树脂的反应活性相对较低;在本发明中,所述凝胶剂的引入有效调控了溶胶的流变行为与交联过程,使得体系能够在150~200℃的较低温度下发生可控的凝胶化,例如在4~9h内可以形成具有均匀的三维网络结构的湿凝胶,这是最终获得低密度、高孔隙率气凝胶的关键结构基础之一,若不加入所述凝胶剂,则体系不能完全凝胶;在此基础上,本发明采用梯度溶剂置换策略,通过逐步降低体系的表面张力与极性,有效缓解了溶剂置换过程中因界面张力突变对凝胶网络产生的影响,避免了直接采用单一低沸点溶剂置换可能引发的孔道收缩、开裂或坍塌,从而最大限度地保留了湿凝胶在凝胶化阶段形成的三维纳米多孔结构;本发明工艺确保了最终所得邻苯二甲腈气凝胶具有低密度和均匀的纳米多孔结构,同时依托邻苯二甲腈树脂的耐高温特性,使制得的邻苯二甲腈树脂气凝胶及其复合材料实现了超轻质、高效隔热、高力学强度、优异耐高温性等特点,拓展了其在高温隔热、航空航天等领域的应用潜力。
Smart Images

Figure CN121930540B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aerogel and its product preparation technology, and particularly relates to a lightweight ceramizable phthalonitrile aerogel, its composite material and preparation method. Background Technology
[0002] Human aerospace activities are undergoing profound changes towards extreme environments and reusable models, placing unprecedentedly high demands on thermal protection systems. Especially on the leeward side of supersonic vehicles, materials must withstand prolonged and repeated exposure to coupled thermal, mechanical, and airflow loads in low-to-medium temperature environments, simultaneously meeting stringent comprehensive requirements such as high-efficiency thermal insulation, mechanical strength, erosion resistance, thermal stability, fatigue resistance, and lightweight properties. Therefore, developing a new generation of thermal protection materials that combine lightweight, long-lasting thermal insulation, high-temperature resistance, fatigue resistance, and reusability has become an urgent need to overcome technological bottlenecks and support the development of future advanced aerospace vehicles.
[0003] Aerogels, due to their ultra-low density, high porosity, and low thermal conductivity, have broad application prospects in fields such as thermal insulation, catalysis, and energy. Traditional inorganic or organic polymer aerogels generally face bottlenecks such as poor mechanical properties and insufficient high-temperature stability. Phthalonil resin, with its excellent thermal stability, high char residue, and superior mechanical properties, is considered an ideal precursor for preparing high-temperature resistant aerogels.
[0004] However, phthalonitrile resins have high curing temperatures and long curing cycles, making it difficult to precisely control their sol-gel process. This poses a significant challenge to the direct preparation of high-performance aerogels with uniform structure, adjustable density, and complete nanonetworks. Existing technologies cannot directly prepare phthalonitrile aerogels with complete nanonetwork structures using phthalonitrile resins. Chinese patent application CN119192658A uses a phthalonitrile monomer and ionic liquid system to prepare aerogels through gradient temperature curing. Although it achieves certain mechanical strength and low shrinkage, its gelation process relies on high-temperature, long-term thermal curing, resulting in a long reaction cycle. Furthermore, the resulting aerogels have relatively high density and limited pore structure control, making it difficult to achieve ultra-lightweight properties and precise control of the gelation process. This makes it difficult to meet the requirements of weight reduction, short preparation cycle, and low thermal conductivity for thermal protection materials. Chinese patent application CN119859311A, by introducing phthalonitrile into a phenolic resin system to prepare modified aerogels, improved the material's thermal stability and residual carbon content. However, it is still based on the traditional phenolic system, which suffers from slow curing reaction, limited crosslinking density, and a complex mixed solvent system, making it difficult to control the gelation rate and resulting in a high final material density. This also fails to meet the requirements for lightweight and rapid preparation. Chinese patent application CN120795323A focuses on the synthesis of organosilicon-modified phthalonitrile resins and the improvement of composite material processing performance, addressing the resin's flowability and processability issues. It is suitable for molding composite materials such as laminates, but it does not involve the aerogel system and lacks the construction and control of the porous network structure, thus failing to achieve ultra-lightweight thermal insulation. None of the above patent applications have achieved effective control over the gel network structure and / or density while ensuring the material's lightweight properties, thus restricting the application expansion of phthalonitrile resin materials in the field of high-performance aerogels. Currently, there is still a lack of a method for preparing phthalonitrile aerogels and their composites that can achieve dual control over density and gelation process, and possess ultra-lightweight, high-efficiency thermal insulation, high mechanical strength, excellent high-temperature resistance, and ceramicizability.
[0005] Therefore, there is an urgent need to provide a lightweight, ceramicizable phthalonitrile aerogel with controllable density and gelation, its composite materials, and a preparation method. Summary of the Invention
[0006] To address one or more technical problems existing in the prior art, this invention provides a lightweight, ceramicizable phthalonitrile aerogel, its composite material, and a preparation method thereof.
[0007] The present invention provides a method for preparing a lightweight, ceramizable phthalonitrile aerogel in a first aspect, the method comprising the following steps: (1) Mix phthalonitrile resin, gelling agent, polar aprotic solvent and curing agent evenly to obtain sol; (2) The sol is gelled at 150~200℃ to obtain a wet gel; (3) The wet gel was subjected to gradient solvent replacement, drying and curing in sequence to obtain a lightweight ceramizable phthalonitrile aerogel.
[0008] In a second aspect, the present invention provides a method for preparing a lightweight, ceramizable phthalonitrile aerogel composite material, the method comprising the following steps: (a) Dissolve phthalonitrile resin and gelling agent in a polar aprotic solvent and add curing agent and mix evenly to obtain sol; (b) Impregnate the fiber preform with sol and then gel at 150~200℃ to obtain a wet gel; (c) The wet gel was subjected to gradient solvent replacement, drying and curing in sequence to obtain a lightweight phthalonitrile aerogel composite material that can be ceramicized.
[0009] Preferably, the gelation time is 4-9 hours, more preferably 6-8 hours; the gelling agent is one or more of polymeric ceramic precursors, organosilanes, and silicone resins; preferably, the organosilane is one or more of tetraethyl orthosilicate, methyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-glycidyl etheroxypropyltrimethoxysilane, and 3-methacryloyloxypropyltrimethoxysilane; the polar aprotic solvent is one or more of N-methylpyrrolidone, ethyl acetate, dimethyl sulfoxide, dimethylformamide, and acetone; and / or the curing agent is one or more of sodium bicarbonate, m-phenylenediamine, bisphenol A, bisphenol F, diaminobenzoic acid, 4,4'-diaminodiphenyl sulfone, sodium hydroxide, potassium hydroxide, hexamethylenetetramine, and diaminotoluene.
[0010] Preferably, in step (1) and / or step (a), a catalyst is also added to the sol; preferably, the catalyst is one or more of zinc chloride, aluminum chloride, and benzothiazole.
[0011] Preferably, the mass ratio of the phthalonitrile resin to the polar aprotic solvent is 1:(3~8); the mass ratio of the gelling agent to the phthalonitrile resin is 1:(1~20), preferably 1:(5~20); and / or the mass ratio of the curing agent to the phthalonitrile resin is 1:(20~60).
[0012] Preferably, the heating rate of the gel is 1~5℃ / min, more preferably 3~5℃ / min.
[0013] Preferably, the gradient solvent replacement sequentially includes: replacing at least once with a mixed solvent containing 70-80 vol% of a first solvent and 20-30 vol% of a second solvent; replacing at least once with a mixed solvent containing 20-50 vol% of a first solvent and 50-80 vol% of a second solvent; and replacing at least once with a second solvent; preferably, the first solvent is acetone, and the second solvent is one or more of ethanol, tert-butanol, and isopropanol; preferably, the replacement time is 6-12 hours.
[0014] Preferably, the drying temperature is 40~80℃ and the drying time is 12~36h; and / or the curing temperature is 250~350℃ and the curing time is 12~18h; preferably, the curing heating rate is 1~5℃ / min, more preferably 1~3℃ / min.
[0015] Preferably, the impregnation is vacuum impregnation, and more preferably, the vacuum impregnation temperature is 20~30℃, the vacuum degree of the vacuum impregnation is -0.03~-0.1MPa, and the vacuum impregnation time is 60~120min; the fiber preform is one or more of carbon fiber preform, quartz fiber preform, mullite fiber preform, and glass fiber preform; and / or the structure of the fiber preform is one or more of fiber needle-punched felt, 2.5D fabric, and 3D fabric.
[0016] In a third aspect, the present invention provides a lightweight ceramizable phthalonitrile aerogel prepared by the preparation method described in the first aspect of the present invention, or a lightweight ceramizable phthalonitrile aerogel composite material prepared by the preparation method described in the second aspect of the present invention.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects: (1) This invention overcomes the technical obstacle of failing to form a stable gel system by simply dispersing phthalonitrile resin and adding a curing agent in a polar aprotic solvent and then mixing them with a curing agent to form a sol. This is because phthalonitrile resin is different from phthalonitrile monomers, and the reactivity of phthalonitrile resin is relatively low. In this invention, the introduction of the gelling agent effectively regulates the rheological behavior and cross-linking process of the sol, enabling the system to undergo controllable gelation at a relatively low temperature of 150~200℃. For example, a wet gel with a uniform three-dimensional network structure can be formed within 4~9h. This is one of the key structural foundations for finally obtaining a low-density, high-porosity aerogel. If the gelling agent is not added, the system cannot be completely gelled. Based on this, the present invention adopts a gradient solvent replacement strategy, which effectively mitigates the impact of sudden changes in interfacial tension on the gel network during solvent replacement by gradually reducing the surface tension and polarity of the system. This avoids the pore shrinkage, cracking or collapse that may be caused by directly using a single low-boiling-point solvent for replacement, thereby maximizing the preservation of the three-dimensional nanoporous structure formed by the wet gel during the gelation stage. The process of the present invention ensures that the final phthalonitrile aerogel has a low-density and uniform nanoporous structure. At the same time, relying on the high-temperature resistance of phthalonitrile resin, the prepared phthalonitrile resin aerogel and its composite materials achieve ultra-lightweight, high-efficiency thermal insulation, high mechanical strength and excellent high-temperature resistance, expanding its application potential in high-temperature thermal insulation, aerospace and other fields.
[0018] (2) In this invention, the gelling agent is selected from one or more of polymer-type ceramic precursors, organosilanes, and silicone resins. This design achieves a beneficial combination of dual functions: on the one hand, these components can effectively regulate the gelation behavior of the sol, enabling it to undergo controllable gelation at a relatively low temperature of 150~200℃, forming a stable three-dimensional network framework, which is the key to obtaining a lightweight, high-porosity aerogel structure; on the other hand, these gelling agents themselves are introduced into the gel network as ceramicizable components, and can be transformed in situ into high-temperature resistant ceramic phases (such as SiO2, SiOC, etc.) during subsequent high-temperature treatment, improving the thermal decomposition temperature and high-temperature resistance of the material, thereby significantly improving the performance of phthalic acid. The phthalonitrile aerogel and its composites exhibit excellent overall thermal stability, oxidation resistance, and high-temperature strength. The unique "ceramizationable" property of this invention allows the organic network to partially transform into an inorganic ceramic network when exposed to high temperatures (e.g., ≥800℃), preventing dripping or collapse and effectively maintaining structural integrity and thermal insulation performance, providing "damage-tolerant" thermal protection. This "dual-effect" design not only solves the problems of easy pyrolysis and collapse of purely organic resin-based aerogels at medium and high temperatures, and the high brittleness and poor thermal shock resistance of inorganic aerogels, but also enables the resulting phthalonitrile aerogel and its composites to possess excellent ablation insulation performance in complex thermo-mechanical-gas flow multi-field coupling environments. The aerogel matrix of this invention is a high-performance phthalonitrile resin, endowing the material with excellent long-term reusability at medium and low temperatures (stable in air above 350℃), ablation insulation at extremely high temperatures, and flame retardancy. It achieves a comprehensive balance of lightweight, thermal insulation, strength, and reusability, meeting the stringent requirements of advanced thermal protection materials.
[0019] (3) In some preferred embodiments of the present invention, the phthalonitrile aerogel prepared is preferably controlled more precisely by synergistic optimization of molecular design (phthalonitrile resin / gelant mass ratio, sol solid content) and process parameters (gel temperature, gradient solvent replacement process and high temperature curing temperature), thereby enabling the present invention to prepare a series of phthalonitrile aerogels with continuously adjustable density (ultra-light to medium-high density), designable pore size distribution, and while maintaining high specific surface area and excellent mechanical strength, meeting the stringent requirements of material density for different application scenarios. Using the method of the present invention, a series of phthalonitrile aerogels with a density of 0.05 g / cm³ can be prepared. 3 Up to 0.15 g / cm 3 A lightweight, high-performance phthalonitrile aerogel with a continuously adjustable and uniform structure within a certain range.
[0020] (4) The phthalonitrile aerogel composites prepared by this invention can achieve good bonding between the aerogel matrix and the fiber preform. The resulting phthalonitrile aerogel composites have the characteristics of being lightweight, high-strength, and having excellent high-temperature resistance. The lightweight ceramizable phthalonitrile aerogels and their composites prepared by this invention are particularly suitable for fields that are sensitive to weight and need to withstand extreme high temperatures, such as designable gradient thermal insulation layers for aerospace vehicles and lightweight large-area thermal protection systems for hypersonic vehicles. The method of this invention has strong process controllability and can precisely control the density and microstructure of phthalonitrile aerogels. The method of this invention not only improves the preparation efficiency but also significantly reduces the shrinkage rate of the material, improves the mechanical properties and ease of processing of the material in the later stage, and the properties of the material obtained by this invention can be designed, which has important application value in high-end thermal protection systems in aerospace and other fields. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the embodiments will be briefly described below. Obviously, the drawings described below are some embodiments of the present invention and are only used to more clearly illustrate the technical solutions of the embodiments of the present invention, so they should not be regarded as a limitation of the scope. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a flowchart illustrating the preparation process of some specific embodiments of the present invention; Figure 2 This is a microscopic morphology image of the lightweight, ceramizable phthalonitrile aerogel prepared in Example 1 of this invention; Figure 3 This is a macroscopic photograph of the lightweight, ceramizable phthalonitrile aerogel composite material prepared according to the present invention; Figure 4 This is the mechanical compression performance curve of the lightweight, ceramizable phthalonitrile aerogel composite material prepared in Example 10 of the present invention. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments thereof. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0024] The present invention provides, in a first aspect, a method for preparing a lightweight, ceramizable phthalonitrile aerogel (abbreviated as phthalonitrile aerogel), with a preparation flow chart, for example, as follows. Figure 1 As shown, the preparation method includes the following steps: (1) The phthalonitrile resin, gelling agent, polar aprotic solvent and curing agent are mixed evenly to obtain a sol; the phthalonitrile resin is not specifically limited in this invention, and powdered phthalonitrile resin that can be purchased directly from the market can be used; specifically, step (1) is, for example: the phthalonitrile resin and gelling agent are dissolved in a polar aprotic solvent at a certain mass ratio, and after they are dissolved, the curing agent is added and stirred evenly to obtain a sol; or the phthalonitrile resin, gelling agent, polar aprotic solvent and curing agent are stirred evenly at room temperature to obtain a uniformly mixed sol; in this invention, the room temperature is, for example, 15~35℃; (2) The sol is gelled at 150~200℃ (e.g. 150℃, 160℃, 170℃, 180℃, 190℃ or 200℃) to obtain a wet gel; (3) The wet gel is subjected to gradient solvent replacement, drying and curing in sequence to obtain a lightweight ceramizable phthalonitrile aerogel; In this invention, the gelation, gradient solvent replacement and curing are all carried out in a closed environment, for example, in a sealed container.
[0025] This invention overcomes the technical obstacle of failing to form a stable gel system by simply dispersing phthalonitrile resin and adding a curing agent in a polar aprotic solvent to form a sol. This is because phthalonitrile resin differs from phthalonitrile monomers, exhibiting relatively low reactivity. In this invention, the introduction of the gelling agent effectively regulates the rheological behavior and crosslinking process of the sol, enabling the system to undergo controllable gelation at relatively low temperatures of 150-200°C. For example, a wet gel with a uniform three-dimensional network structure can be formed within 4-9 hours. This is one of the key structural foundations for ultimately obtaining low-density, high-porosity aerogels. Without the gelling agent, the system cannot gel completely. In this invention, the gelation temperature is 150~200℃, and the time is 4~9h. This invention found that if the temperature is too low, the cross-linking reaction rate will be too slow, making it difficult to form a complete and sufficiently strong three-dimensional network structure. This results in a loose wet gel skeleton, incomplete gelation, or easy collapse and shrinkage during subsequent drying and curing, making it impossible to prepare low-density, high-porosity aerogels. On the other hand, if the gelation temperature is too high, the reaction rate will be too fast, causing intense local cross-linking and resulting in a broken network structure. Inhomogeneity and internal stress concentration can induce cracks or coarsening of pores, disrupting the stability of the sol and the fine control of pore structure. If the gelation time is too short, insufficient cross-linking can lead to a fragile gel network, incomplete gelation, or structural collapse during subsequent processing. Conversely, excessive gelation time can cause over-cross-linking, making the gel brittle, reducing porosity, and leading to irreversible densification, forming large or irregular pores, significantly increasing material density, and weakening its lightweight and thermal insulation properties. Therefore, this invention employs a gradient solvent replacement strategy, gradually reducing the surface tension and polarity of the system to effectively alleviate solvent stress. The process avoids the impact of sudden changes in interfacial tension on the gel network during the replacement process, thus preventing the pore shrinkage, cracking, or collapse that may be caused by direct replacement with a single low-boiling-point solvent. This maximizes the preservation of the three-dimensional nanoporous structure formed by the wet gel during the gelation stage. The process of this invention ensures that the final phthalonitrile aerogel has a low-density and uniform nanoporous structure. At the same time, relying on the high-temperature resistance of phthalonitrile resin, the prepared phthalonitrile resin aerogel and its composite materials achieve ultra-lightweight, high-efficiency thermal insulation, high mechanical strength, and excellent high-temperature resistance, expanding its application potential in high-temperature thermal insulation, aerospace and other fields.
[0026] This invention directly prepares aerogels using phthalonitrile resin. Compared to existing methods that use phthalonitrile monomers and ionic liquids to prepare aerogels, this invention offers significant advantages in achieving lightweight, controllable gelation, and high-efficiency thermal insulation. This is because, with the aid of a gelling agent, phthalonitrile resin can rapidly form a stable and uniform three-dimensional network framework in the sol stage, which is beneficial for constructing a highly interconnected nanoporous structure, thus making it easier to obtain lightweight aerogels with low density and high porosity. Simultaneously, the phthalonitrile resin system used in this invention avoids the uncontrollability of the reaction caused by the gradual polymerization of monomers from a low molecular weight state. The gelation process does not require a slow growth stage, the crosslinking rate is stable, significantly improving the controllability and batch consistency of the gel, and shortening the gelation time, thereby increasing preparation efficiency. Furthermore, this uniform network structure helps maintain pore integrity, giving the aerogel lower thermal conductivity and superior thermal insulation performance.
[0027] In a second aspect, this invention provides a method for preparing a lightweight, ceramizable phthalonitrile aerogel composite material (abbreviated as phthalonitrile aerogel composite material), the preparation process of which is illustrated in, for example, as shown in the flowchart. Figure 1 As shown, the preparation method includes the following steps: (a) Phthalonil resin, gelling agent, polar aprotic solvent and curing agent are mixed evenly to obtain a sol; the present invention does not specifically limit the phthalonitrile resin, and commercially available powdered phthalonitrile resin can be used; specifically, step (a) is, for example: phthalonitrile resin and gelling agent are dissolved in a polar aprotic solvent at a certain mass ratio, and after they are dissolved, the curing agent is added and stirred evenly to obtain a sol; or phthalonitrile resin, gelling agent, polar aprotic solvent and curing agent are directly stirred evenly at room temperature to obtain a uniformly mixed sol; (b) Impregnate the fiber preform with a sol, and then gel at 150-200°C (e.g., 150°C, 160°C, 170°C, 180°C, 190°C, or 200°C) to obtain a wet gel; in this invention, for example, the fiber preform is immersed in the sol, and vacuum-assisted impregnation is used to ensure that the sol fully wets the fiber, and then the impregnated fiber preform is gelled at 150-200°C for 6-8 hours to obtain a wet gel; in this invention, after impregnating the fiber preform with the sol, it is not necessary to remove the fiber preform from the sol, but rather the fiber preform is impregnated in the sol and gelled in situ at 150-200°C; (c) The wet gel was subjected to gradient solvent replacement, drying and curing in sequence to obtain a lightweight phthalonitrile aerogel composite material that can be ceramicized.
[0028] The phthalonitrile aerogel composites prepared by this invention achieve excellent bonding between the aerogel matrix and the fiber preform. The resulting phthalonitrile aerogel composites possess lightweight, high strength, and excellent high-temperature resistance. The lightweight, ceramizable phthalonitrile aerogels and their composites prepared by this invention are particularly suitable for weight-sensitive applications requiring extreme high-temperature resistance, such as designable gradient thermal insulation layers for aerospace vehicles and lightweight, large-area thermal protection systems for hypersonic vehicles. The method of this invention offers strong process controllability, and the properties of the resulting materials can be designed, making it of significant application value in high-end thermal protection systems in aerospace and other fields.
[0029] According to some preferred embodiments, the gelation time is 4 to 9 hours (e.g., 4, 5, 6, 7, 8 or 9 hours), preferably 6 to 8 hours (e.g., 6, 7 or 8 hours).
[0030] According to some preferred embodiments, the gelling agent is one or more of a polymeric ceramic precursor, an organosilane, and a silicone resin; preferably, the organosilane is one or more of tetraethyl orthosilicate, methyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-methacryloyloxypropyltrimethoxysilane; preferably, the polymeric ceramic precursor is one or more of polycarbosilane, polysilazane, polysiloxane, and polyborosilicate; in this invention, the gelling agent is selected from one or more of a polymeric ceramic precursor, an organosilane, and a silicone resin. This design achieves a beneficial combination of dual functions: on the one hand, these components can effectively regulate the gelation behavior of the sol, enabling it to undergo controllable gelation at a relatively low temperature of 150~200℃, forming a stable three-dimensional network framework, which is key to obtaining a lightweight, high-porosity aerogel structure; on the other hand... In this respect, these gelling agents themselves are introduced into the gel network as ceramizable components. During subsequent high-temperature treatment, they can be transformed in situ into high-temperature resistant ceramic phases (such as SiO2, SiOC, etc.), which improves the thermal decomposition temperature and high-temperature resistance of the material. This significantly enhances the overall thermal stability, oxidation resistance, and high-temperature strength of phthalonitrile aerogels and their composites. The unique "ceramizable" characteristic of this invention allows the organic network to be partially transformed into an inorganic ceramic network when the material is exposed to high temperatures (e.g., ≥800℃), without melting or collapse, effectively maintaining structural integrity and thermal insulation performance, and providing "damage-tolerant" thermal protection. This "one agent, two effects" design not only solves the problems of easy thermal decomposition and collapse of simple organic resin-based aerogels at medium and high temperatures, and the high brittleness and poor thermal shock resistance of inorganic aerogels, but also enables the phthalonitrile aerogels and their composites to have excellent ablation thermal insulation performance in complex thermo-mechanical-gas flow multi-field coupling environments. The aerogel matrix of this invention is a high-performance phthalonitrile resin, which gives the material excellent long-term reusability at medium and low temperatures (stable in air above 350°C), ablation insulation and flame retardancy at extremely high temperatures, achieving a comprehensive balance of lightweight, heat insulation, strength and reusability, and meeting the stringent requirements of advanced thermal protection materials.
[0031] According to some preferred embodiments, the polar aprotic solvent is one or more of N-methylpyrrolidone, ethyl acetate, dimethyl sulfoxide, dimethylformamide, and acetone; and / or the curing agent is one or more of sodium bicarbonate, m-phenylenediamine, bisphenol A (2,2-bis(p-hydroxyphenyl)propane), bisphenol F (4,4-dihydroxydiphenylmethane), diaminobenzoic acid, 4,4'-diaminodiphenyl sulfone, sodium hydroxide, potassium hydroxide, hexamethylenetetramine, and diaminotoluene.
[0032] According to some preferred embodiments, in step (1) and / or step (a), a catalyst is further added to the sol; preferably, the catalyst is one or more of zinc chloride, aluminum chloride, and benzothiazole. In this invention, it is preferable to add the catalyst to the sol, which can further optimize the network structure, so that the final phthalonitrile aerogel has a lower density and higher pore uniformity, thus being more conducive to achieving ultra-lightweight properties; at the same time, the catalyst helps to form a more stable three-dimensional network, further improving the mechanical strength and structural stability of the phthalonitrile aerogel material at high temperatures, giving it efficient thermal insulation performance and excellent high-temperature resistance, and this strengthened cross-linked network can also make the performance of the phthalonitrile aerogel more stable under multiple thermal cycles or stress, which is beneficial to improving reusability.
[0033] According to some preferred embodiments, the mass ratio of the catalyst to the phthalonitrile resin is (0.5~3):100.
[0034] According to some preferred embodiments, the mass ratio of the phthalonitrile resin to the polar aprotic solvent is 1:(3~8) (e.g., 1:3, 1:4, 1:5, 1:6, 1:7 or 1:8), preferably 1:(3~6); the mass ratio of the gelling agent to the phthalonitrile resin is 1:(1~20) (e.g., 1:1, 1:5, 1:10, 1:15 or 1:20), preferably 1:(5~20) (e.g., 1:5, 1:8, 1:10, 1:12, 1:15, 1:18 or 1:20); and / or the mass ratio of the curing agent to the phthalonitrile resin is 1:(20~60) (e.g., 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55 or 1:60).
[0035] In this invention, optimized control of molecular design (phthalonitrile resin / gelant mass ratio, sol solids content, etc.) enables more precise control over the sol-gel transformation kinetics and the final network structure. This facilitates the preparation of a series of phthalonitrile aerogels with continuously tunable density (ultra-light to medium-high density), designable pore size distribution, and while maintaining high specific surface area and excellent mechanical strength. Ultimately, this results in phthalonitrile aerogels with a density of 0.05 g / cm³. 3 Up to 0.15 g / cm 3Controllable adjustment within a certain range is beneficial for obtaining phthalonitrile aerogels with an adjustable pore size distribution ranging from micropores to mesopores. This invention has found that if the sol solid content is too low, the system may not be able to gel completely or the gel network may become sparse and fragile, making the aerogel prone to severe shrinkage or even collapse during drying and curing, resulting in a significant decrease in mechanical strength. On the other hand, if the sol solid content is too high, the sol viscosity will increase sharply, hindering uniform gelation and easily forming a dense non-porous structure, leading to increased material density and deterioration of thermal insulation performance. At the same time, insufficient gelling agent content will slow down the gelation rate, resulting in poor stability of the aerogel network and insufficient high-temperature performance and mechanical strength. On the other hand, excessive gelling agent content may cause the reaction to be too fast, forming local excessive cross-linking and uneven pore size distribution, which not only reduces the specific surface area and uniformity of the material, but may also cause cracking due to internal stress concentration, ultimately affecting the structural uniformity and overall performance reliability of the aerogel.
[0036] According to some preferred embodiments, the heating rate of the gel is 1~5℃ / min (e.g., 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5℃ / min), preferably 3~5℃ / min; in this invention, the heating rate of the gel refers to the heating rate at which the gel temperature rises to 150~200℃.
[0037] According to some preferred embodiments, the gradient solvent replacement sequentially includes: replacing at least once with a mixed solvent containing 70-80 vol% of a first solvent and 20-30 vol% of a second solvent; replacing at least once with a mixed solvent containing 20-50 vol% of a first solvent and 50-80 vol% of a second solvent; and replacing at least once with a second solvent; preferably, the first solvent is acetone, and the second solvent is one or more of ethanol, tert-butanol, and isopropanol; preferably, the replacement time is 6-12 hours (e.g., 6, 7, 8, 9, 10, 11, or 12 hours).
[0038] The present invention preferably employs the above-mentioned gradient solvent replacement. By gradually changing the ratio of the first solvent (acetone) to the second solvent in the mixed solvent, a smooth transition of solvent polarity and surface tension is achieved. By gradually reducing the surface tension and polarity of the system, the influence of the sudden change in interfacial tension on the gel network during the solvent replacement process is effectively mitigated. This avoids the pore shrinkage, cracking or collapse that may be caused by directly using a single low-boiling-point solvent for replacement, thereby maximizing the preservation of the three-dimensional nanoporous structure formed by the wet gel during the gelation stage.
[0039] According to some preferred embodiments, the drying temperature is 40~80°C (e.g., 40°C, 50°C, 60°C, 70°C, or 80°C), and the drying time is 12~36h (e.g., 12, 24, or 36h); and / or the curing temperature is 250~350°C (e.g., 250°C, 300°C, or 350°C), and the curing time is 12~18h (e.g., 12, 15, or 18h). In this invention, a one-step high-temperature curing of the phthalonitrile resin network can be achieved. This process simplifies the complex gradient temperature rise procedure required in the past, ensuring sufficient cross-linking of the resin. While forming a highly stable network structure, this process effectively promotes the transformation of the material into a stable structure at high temperatures. This curing process not only improves preparation efficiency and reduces energy consumption and process complexity, but also produces aerogels with excellent temperature resistance, high-efficiency thermal insulation, mechanical strength, and structural integrity. In this invention, preferably, the curing heating rate is 1~5℃ / min (e.g., 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, or 5℃ / min), preferably 1~3℃ / min. In this invention, the curing heating rate refers to the heating rate at which the material reaches the curing temperature.
[0040] More preferably, the heating rate of the gel is 1~5℃ / min, and the heating rate of the curing is 1~5℃ / min. This is beneficial for the sol to achieve uniform and sufficient molecular self-assembly when forming a three-dimensional network, thereby laying the foundation for a uniform and pore-complete aerogel skeleton. Under the premise of ensuring sufficient cross-linking of the resin, the process efficiency can be effectively improved and the network structure can be further stabilized. Preferably, the microstructure of the material is optimized by precisely controlling the heating rate at different stages. Finally, the obtained phthalonitrile aerogel has a uniform and controllable degree of cross-linking and excellent structural integrity, which is beneficial to improving the thermal insulation performance and comprehensive performance of the phthalonitrile aerogel.
[0041] According to some preferred embodiments, the impregnation is vacuum impregnation. Preferably, the temperature of the vacuum impregnation is 20~30℃, the vacuum degree of the vacuum impregnation is -0.03~-0.1MPa, and the vacuum impregnation time is 60~120min; the fiber preform is one or more of carbon fiber preform, quartz fiber preform, mullite fiber preform, and glass fiber preform; and / or the structure of the fiber preform is one or more of fiber needle-punched felt, 2.5D fabric, and 3D fabric.
[0042] In a third aspect, this invention provides a lightweight, ceramizable phthalonitrile aerogel prepared by the method described in the first aspect, or a lightweight, ceramizable phthalonitrile aerogel composite material prepared by the method described in the second aspect. The lightweight, ceramizable phthalonitrile aerogel or lightweight, ceramizable phthalonitrile aerogel composite material prepared by this invention can be reused repeatedly for extended periods at medium and low temperatures, possessing characteristics of ultra-lightweight, highly efficient thermal insulation, high mechanical strength, excellent high-temperature resistance, and ceramizability. It can be applied in the field of aerospace thermal protection as an advanced lightweight thermal insulation composite material.
[0043] According to some preferred embodiments, the density of the lightweight, ceramizable phthalonitrile aerogel is 0.05~0.15 g / cm³. 3 Preferably, it is 0.1~0.115 g / cm³. 3 The compressive strength at 60% compressive strain is 1.30~1.85 MPa, preferably 1.5~1.85 MPa, TG 5% The thermal decomposition temperature is 440~460℃, and the thermal conductivity at room temperature is 0.03~0.035W / (m·K).
[0044] The present invention will be further described below by way of examples, but the scope of protection of the present invention is not limited to these embodiments. The present invention may have many other embodiments, and those skilled in the art can make various corresponding changes and modifications based on the present invention without departing from its spirit and essence. However, all such corresponding changes and modifications should fall within the scope of protection of the appended claims. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise stated, the raw materials and reagents used in the following embodiments and comparative examples are purchased products or prepared by known methods.
[0045] Example 1
[0046] ① The phthalonitrile resin, the gelling agent tetraethyl orthosilicate, the polar aprotic solvent N-methylpyrrolidone, and the curing agent 4,4'-diaminodiphenyl sulfone were thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent was 1:5, the mass ratio of gelling agent to phthalonitrile resin was 1:10, and the mass ratio of curing agent to phthalonitrile resin was 1:40.
[0047] ② The sol was heated to 170℃ at a heating rate of 3℃ / min and gelled for 8 hours to obtain a wet gel.
[0048] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 80 vol% acetone and 20 vol% anhydrous ethanol; then once with a mixed solvent containing 40 vol% acetone and 60 vol% anhydrous ethanol; and finally once with anhydrous ethanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by heating to 320°C at a heating rate of 1.5°C / min for 18 hours.
[0049] Microstructure of the lightweight, ceramizable phthalonitrile aerogel prepared in Example 1 of this invention, as shown in the figure. Figure 2 As shown; from Figure 2 It can be seen that the present invention has successfully prepared phthalonitrile aerogel with a uniform nanoporous structure.
[0050] Example 2
[0051] ① Phthalonil resin, tetraethyl orthosilicate gelling agent, N-methylpyrrolidone polar aprotic solvent, 4,4'-diaminodiphenyl sulfone curing agent, and zinc chloride catalyst are thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:5, the mass ratio of gelling agent to phthalonitrile resin is 1:10, the mass ratio of curing agent to phthalonitrile resin is 1:40, and the mass ratio of catalyst to phthalonitrile resin is 1.5:100.
[0052] ② The sol was heated to 170℃ at a heating rate of 3℃ / min and gelled for 8 hours to obtain a wet gel.
[0053] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 80 vol% acetone and 20 vol% anhydrous ethanol; then once with a mixed solvent containing 40 vol% acetone and 60 vol% anhydrous ethanol; and finally once with anhydrous ethanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by heating to 320°C at a heating rate of 1.5°C / min for 18 hours.
[0054] Example 3
[0055] ① The phthalonitrile resin, gelling agent (composed of methyltrimethoxysilane and 3-aminopropyltriethoxysilane in a mass ratio of 1:1), polar aprotic solvent dimethyl sulfoxide, and curing agent m-phenylenediamine are thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:5, the mass ratio of gelling agent to phthalonitrile resin is 1:15, and the mass ratio of curing agent to phthalonitrile resin is 1:40.
[0056] ② The sol was heated to 180℃ at a heating rate of 3℃ / min and gelled for 7 hours to obtain a wet gel.
[0057] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 75 vol% acetone and 25 vol% isopropanol; then once with a mixed solvent containing 30 vol% acetone and 70 vol% isopropanol; and finally once with isopropanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by heating to 350°C at a heating rate of 1.5°C / min for 15 hours.
[0058] Example 4
[0059] ① Phthalonil resin, gelling agent (composed of methyltrimethoxysilane and 3-aminopropyltriethoxysilane in a mass ratio of 1:1), polar aprotic solvent dimethyl sulfoxide, curing agent m-phenylenediamine, and catalyst benzothiazole are thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:5, the mass ratio of gelling agent to phthalonitrile resin is 1:15, the mass ratio of curing agent to phthalonitrile resin is 1:40, and the mass ratio of catalyst to phthalonitrile resin is 1.5:100.
[0060] ② The sol was heated to 180℃ at a heating rate of 3℃ / min and gelled for 7 hours to obtain a wet gel.
[0061] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 75 vol% acetone and 25 vol% isopropanol; then once with a mixed solvent containing 30 vol% acetone and 70 vol% isopropanol; and finally once with isopropanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by heating to 350°C at a heating rate of 1.5°C / min for 15 hours.
[0062] Example 5
[0063] ① The phthalonitrile resin, gelling agent (composed of methyltrimethoxysilane and 3-aminopropyltriethoxysilane in a mass ratio of 1:1), polar aprotic solvent dimethyl sulfoxide, and curing agent m-phenylenediamine are thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:3, the mass ratio of gelling agent to phthalonitrile resin is 1:20, and the mass ratio of curing agent to phthalonitrile resin is 1:20.
[0064] ② The sol was heated to 150℃ at a heating rate of 1℃ / min and gelled for 9 hours to obtain a wet gel.
[0065] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel; the gradient solvent replacement was carried out as follows: replacement was performed twice with a mixed solvent containing 70 vol% acetone and 30 vol% isopropanol; then replacement was performed twice with a mixed solvent containing 20 vol% acetone and 80 vol% isopropanol; finally, replacement was performed twice with isopropanol; each replacement lasted for 6 hours; the drying was carried out at 70°C for 24 hours; the curing was carried out by heating to 250°C at a heating rate of 1°C / min for 18 hours.
[0066] Example 6
[0067] ① The phthalonitrile resin, gelling agent (composed of methyltrimethoxysilane and 3-aminopropyltriethoxysilane in a mass ratio of 1:1), polar aprotic solvent dimethyl sulfoxide, and curing agent m-phenylenediamine are thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:8, the mass ratio of gelling agent to phthalonitrile resin is 1:1, and the mass ratio of curing agent to phthalonitrile resin is 1:60.
[0068] ② The sol was heated to 200℃ at a heating rate of 5℃ / min and gelled for 4 hours to obtain a wet gel.
[0069] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 80 vol% acetone and 20 vol% isopropanol; then once with a mixed solvent containing 50 vol% acetone and 50 vol% isopropanol; and finally once with isopropanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by heating to 350°C at a heating rate of 5°C / min for 12 hours.
[0070] Example 7
[0071] ① Phthalonil resin, gelling agent (polymer-type ceramic precursor polycarbosilane), polar aprotic solvent dimethyl sulfoxide, curing agent m-phenylenediamine, and catalyst benzothiazole are thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:5, the mass ratio of gelling agent to phthalonitrile resin is 1:15, the mass ratio of curing agent to phthalonitrile resin is 1:40, and the mass ratio of catalyst to phthalonitrile resin is 1.5:100.
[0072] ② The sol was heated to 180℃ at a heating rate of 3℃ / min and gelled for 7 hours to obtain a wet gel.
[0073] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 75 vol% acetone and 25 vol% isopropanol; then once with a mixed solvent containing 30 vol% acetone and 70 vol% isopropanol; and finally once with isopropanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by heating to 350°C at a heating rate of 1.5°C / min for 15 hours.
[0074] Example 8
[0075] ① Phthalonil resin, gelling agent (epoxy-modified silicone resin), polar aprotic solvent N-methylpyrrolidone, curing agent m-phenylenediamine, and catalyst benzothiazole are thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:5, the mass ratio of gelling agent to phthalonitrile resin is 1:15, the mass ratio of curing agent to phthalonitrile resin is 1:40, and the mass ratio of catalyst to phthalonitrile resin is 1.5:100.
[0076] ② The sol was heated to 180℃ at a heating rate of 3℃ / min and gelled for 7 hours to obtain a wet gel.
[0077] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 75 vol% acetone and 25 vol% isopropanol; then once with a mixed solvent containing 30 vol% acetone and 70 vol% isopropanol; and finally once with isopropanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by heating to 350°C at a heating rate of 1.5°C / min for 15 hours.
[0078] Example 9
[0079] Example 9 is basically the same as Example 3, except that: ② The sol was placed directly at 180℃ for 7 hours to obtain a wet gel.
[0080] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 75 vol% acetone and 25 vol% isopropanol; then once with a mixed solvent containing 30 vol% acetone and 70 vol% isopropanol; and finally once with isopropanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by directly placing it at 350°C for 15 hours.
[0081] Example 10
[0082] ① Phthalonil resin, tetraethyl orthosilicate gelling agent, N-methylpyrrolidone polar aprotic solvent, 4,4'-diaminodiphenyl sulfone curing agent, and zinc chloride catalyst are thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:5, the mass ratio of gelling agent to phthalonitrile resin is 1:10, the mass ratio of curing agent to phthalonitrile resin is 1:40, and the mass ratio of catalyst to phthalonitrile resin is 1.5:100.
[0083] ②Impregnate the quartz fiber preform (quartz fiber needle-punched felt) with sol, and then heat it to 170℃ at a heating rate of 3℃ / min for 8 hours to obtain a wet gel; the impregnation is vacuum impregnation, the temperature of the vacuum impregnation is 25℃, the vacuum degree of the vacuum impregnation is -0.08MPa, and the vacuum impregnation time is 90min.
[0084] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel composite material; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 80 vol% acetone and 20 vol% anhydrous ethanol; then once with a mixed solvent containing 40 vol% acetone and 60 vol% anhydrous ethanol; and finally once with anhydrous ethanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by heating to 320°C at a heating rate of 1.5°C / min for 18 hours.
[0085] Example 11
[0086] ① Phthalonil resin, gelling agent (composed of methyltrimethoxysilane and 3-aminopropyltriethoxysilane in a mass ratio of 1:1), polar aprotic solvent dimethyl sulfoxide, curing agent m-phenylenediamine, and catalyst benzothiazole are thoroughly stirred at room temperature to obtain a uniformly mixed sol; wherein, the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:5, the mass ratio of gelling agent to phthalonitrile resin is 1:15, the mass ratio of curing agent to phthalonitrile resin is 1:40, and the mass ratio of catalyst to phthalonitrile resin is 1.5:100.
[0087] ②Impregnate the quartz fiber preform (quartz fiber needle-punched felt) with sol, and then heat it to 180℃ at a heating rate of 3℃ / min for 7h to obtain a wet gel; the impregnation is vacuum impregnation, the temperature of the vacuum impregnation is 25℃, the vacuum degree of the vacuum impregnation is -0.08MPa, and the vacuum impregnation time is 90min.
[0088] ③ The wet gel was subjected to gradient solvent replacement, drying, and curing in sequence to obtain a lightweight, ceramicizable phthalonitrile aerogel composite material; the gradient solvent replacement was carried out as follows: once with a mixed solvent containing 75 vol% acetone and 25 vol% isopropanol; then once with a mixed solvent containing 30 vol% acetone and 70 vol% isopropanol; and finally once with isopropanol; each replacement lasted for 12 hours; the drying was carried out at 70°C for 24 hours; and the curing was carried out by heating to 350°C at a heating rate of 1.5°C / min for 15 hours.
[0089] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that: ③ The wet gel was subjected to solvent replacement, drying and curing in sequence to obtain a lightweight ceramizable phthalonitrile aerogel; the solvent replacement was carried out by directly replacing the wet gel with acetone solvent three times; the replacement time was 12h each time; the drying was carried out at 70℃ for 24h; the curing was carried out by heating to 320℃ at a heating rate of 1.5℃ / min and curing for 18h.
[0090] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that: ③ The wet gel was subjected to solvent replacement, drying and curing in sequence to obtain a lightweight ceramizable phthalonitrile aerogel; the solvent replacement was carried out by directly replacing the wet gel with anhydrous ethanol solvent three times; the replacement time was 12h each time; the drying was carried out at 70℃ for 24h; the curing was carried out by heating to 320℃ at a heating rate of 1.5℃ / min and curing for 18h.
[0091] Comparative Example 3 Comparative Example 3 prepared phthalonitrile aerogel according to Example 5 of CN119192658A.
[0092] Comparative Example 4 Comparative Example 4 is basically the same as Example 3, except that: ② The sol was heated to 250℃ at a heating rate of 3℃ / min and gelled for 10 hours to obtain a wet gel.
[0093] Comparative Example 5 Comparative Example 5 is basically the same as Example 3, except that: ② Heat the sol to 120℃ at a heating rate of 3℃ / min and gel for 3 hours.
[0094] In this comparative example, the system could not completely gel.
[0095] Comparative Example 6 Comparative Example 6 is basically the same as Example 1, except that: In step ①, the gelling agent was not added.
[0096] In this comparative example, the system could not completely gel.
[0097] Comparative Example 7 Comparative Example 7 is basically the same as Example 3, except that: In step ①, the gelling agent was not added.
[0098] In this comparative example, the system could not completely gel.
[0099] The performance of the materials finally prepared in each embodiment and comparative examples 1 to 4 was tested, and the results are shown in Table 1. The method for the repeated 20-cycle compressive strength retention test was as follows: the material was heat-treated at 350°C for 30 minutes using a hot platform, and then cooled to room temperature. This process was recorded as one test; this process was repeated a total of 20 times.
[0100] Table 1 In Table 1, the symbol "-" indicates that the performance metric was not tested.
[0101] The results in Table 1 show that the introduction of a gelling agent can achieve effective gelation of phthalonitrile aerogels, and the appropriate amount of gelling agent can control the gelation time, which is beneficial to promoting the formation of the three-dimensional network structure inside the aerogel. This is mainly because the gelling agent promotes the gelation reaction during the gelation process, further enhancing the strength of the cross-linked skeleton. In addition, the addition of the gelling agent increases the thermal decomposition temperature and temperature resistance of the material. The lightweight, ceramizable phthalonitrile aerogel and its composite materials prepared by this invention have a controllable gelation process, a high thermal decomposition temperature, excellent mechanical properties, and high-efficiency thermal insulation performance, and can be repeatedly used for a long time in high-temperature environments. The phthalonitrile aerogel material prepared by this invention can still achieve a compressive strength (compressive stress) of 1.3~1.85 MPa while maintaining extremely low density and excellent thermal insulation performance, fully demonstrating its unique advantages and practical value in lightweight and high-efficiency thermal insulation materials.
[0102] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a lightweight, ceramizable phthalonitrile aerogel, characterized in that, The preparation method includes the following steps: (1) Phthalonil resin, gelling agent, polar aprotic solvent and curing agent are mixed evenly to obtain a sol; the gelling agent is one or more of polymer-type ceramic precursor, organosilane, and silicone resin; the curing agent is one or more of sodium bicarbonate, m-phenylenediamine, bisphenol A, bisphenol F, diaminobenzoic acid, 4,4'-diaminodiphenyl sulfone, sodium hydroxide, potassium hydroxide, hexamethylenetetramine, and diaminotoluene; the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:(3~8); the mass ratio of gelling agent to phthalonitrile resin is 1:(1~20); the mass ratio of curing agent to phthalonitrile resin is 1:(20~60). (2) The sol is gelled at 150~200℃ to obtain a wet gel; the gelation time is 4~9h; the heating rate of the gel is 1~5℃ / min; (3) The wet gel was subjected to gradient solvent replacement, drying and curing in sequence to obtain a lightweight ceramizable phthalonitrile aerogel; The gradient solvent replacement includes, in sequence: Replace at least once with a mixed solvent containing 70-80 vol% of the first solvent and 20-30 vol% of the second solvent; Replace at least once with a mixed solvent containing 20-50 vol% of a first solvent and 50-80 vol% of a second solvent; and Use a second solvent for displacement at least once; The first solvent is acetone, and the second solvent is one or more of ethanol, tert-butanol, and isopropanol.
2. A method for preparing a lightweight, ceramizable phthalonitrile aerogel composite material, characterized in that, The preparation method includes the following steps: (a) Phthalonil resin and a gelling agent are dissolved in a polar aprotic solvent and a curing agent is added and mixed evenly to obtain a sol; the gelling agent is one or more of a polymeric ceramic precursor, organosilane, and silicone resin; the curing agent is one or more of sodium bicarbonate, m-phenylenediamine, bisphenol A, bisphenol F, diaminobenzoic acid, 4,4'-diaminodiphenyl sulfone, sodium hydroxide, potassium hydroxide, hexamethylenetetramine, and diaminotoluene; the mass ratio of phthalonitrile resin to polar aprotic solvent is 1:(3~8); the mass ratio of gelling agent to phthalonitrile resin is 1:(1~20); the mass ratio of curing agent to phthalonitrile resin is 1:(20~60). (b) The fiber preform is impregnated with sol and then gelled at 150~200℃ to obtain a wet gel; the gelation time is 4~9h; the heating rate of the gel is 1~5℃ / min. (c) The wet gel was subjected to gradient solvent replacement, drying and curing in sequence to obtain a lightweight ceramizable phthalonitrile aerogel composite material; The gradient solvent replacement includes, in sequence: Replace at least once with a mixed solvent containing 70-80 vol% of the first solvent and 20-30 vol% of the second solvent; Replace at least once with a mixed solvent containing 20-50 vol% of a first solvent and 50-80 vol% of a second solvent; and Use a second solvent for displacement at least once; The first solvent is acetone, and the second solvent is one or more of ethanol, tert-butanol, and isopropanol.
3. The preparation method according to claim 1 or 2, characterized in that: The gelation time is 6-8 hours; The organosilane is one or more of tetraethyl orthosilicate, methyltrimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-methacryloyloxypropyltrimethoxysilane. The polar aprotic solvent is one or more of N-methylpyrrolidone, ethyl acetate, dimethyl sulfoxide, dimethylformamide, and acetone.
4. The preparation method according to claim 1 or 2, characterized in that: In step (1) and / or step (a), a catalyst is also added to the sol.
5. The preparation method according to claim 4, characterized in that: The catalyst is one or more of zinc chloride, aluminum chloride, and benzothiazole.
6. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the gelling agent to the phthalonitrile resin is 1:(5~20).
7. The preparation method according to claim 1 or 2, characterized in that: The heating rate of the gel is 3~5℃ / min.
8. The preparation method according to claim 1 or 2, characterized in that: Each replacement takes 6 to 12 hours.
9. The preparation method according to claim 1 or 2, characterized in that: The drying temperature is 40~80℃, and the drying time is 12~36h; and / or The curing temperature is 250~350℃, and the curing time is 12~18h.
10. The preparation method according to claim 9, characterized in that: The curing heating rate is 1~5℃ / min.
11. The preparation method according to claim 10, characterized in that: The curing temperature rise rate is 1~3℃ / min.
12. The preparation method according to claim 2, characterized in that: The impregnation is a vacuum impregnation; The fiber preform is one or more of carbon fiber preform, quartz fiber preform, mullite fiber preform, and glass fiber preform; and / or The structure of the fiber preform is one or more of the following: fiber needle-punched felt, 2.5D fabric, and 3D fabric.
13. The preparation method according to claim 12, characterized in that: The vacuum impregnation temperature is 20~30℃, the vacuum degree of the vacuum impregnation is -0.03~-0.1MPa, and the vacuum impregnation time is 60~120min.
14. A lightweight, ceramizable phthalonitrile aerogel prepared by the method of any one of claims 1 or 3 to 11.
15. A lightweight, ceramizable phthalonitrile aerogel composite material prepared by any one of claims 2 to 13.
Citation Information
Patent Citations
Phthalonitrile modified phenolic aerogel as well as preparation method and application thereof
CN119859311A
Organic silicon modified phthalonitrile resin as well as preparation method and application thereof
CN120795323A
Phthalonitrile aerogel as well as preparation method and application thereof
CN119192658A
SiBCN aerogel as well as normal-pressure drying preparation method and application thereof
CN120157090A